ARTIKEL PEMANFAATAN MEDIA PODCAST DALAM PEMBELAJARAN UNTUK MENINGKATKAN KETERAMPILAN BERBICARA SISWA SEKOLAH DASAR - Khoirunnisa, Anna; Nurazizah, Alya; Habibi, M (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the utilization of podcast media in learning to improve the speaking skills of elementary school students. The study employed a qualitative approach using a literature review method of ten scientific journal articles related to the use of podcasts in elementary school learning. Data were obtained from several databases, namely Google Scholar, Garuda, SINTA, and Publish or Perish. Data analysis was conducted descriptively by reviewing, comparing, and interpreting the findings of previous studies. The results showed that podcast media are effective in improving students’ speaking skills, including speaking fluency, pronunciation accuracy, intonation, self-confidence, and the ability to express ideas orally. In addition, podcasts are able to create a more engaging and flexible learning environment, thereby increasing students’ participation in the learning process. Podcast media also help students understand speaking materials more easily through audio that can be replayed repeatedly according to students’ learning needs. Therefore, podcasts can be used as an innovative alternative learning medium to support the development of elementary school students’ speaking skills.